Open innovation session as a tool supporting innovativeness in strategies for high-tech companies in the Czech Republic - Pavla Matulova; Petra Maresova; Mohammad Ali Tareq; Kamil Kuča (Economies, 2018)
Open innovation has developed over several decades from a small pool of innovation pioneers, mostly active in high-tech industries, to be widely discussed and implemented in innovation strategy. The primary objective of the Open Innovation Session (OIS) is to create a platform where firms are able to facilitate knowledge transfer. This paper focuses on the contribution of OIS, implemented by regional government, in formulating companies' strategic management and to overcome barriers to innovation for high-tech companies in the South Moravian region of the Czech Republic. The methodology adopted for this paper includes monitoring and analysing the activities of this programme over seven years, followed by a quantitative study using both primary and secondary data. The primary data for the research were gathered through questionnaires, where the respondents were general managers of companies that had at least some experience of an innovation process. Secondary data were taken from the Czech Statistical Office. This paper has found that the association between an aspiration for innovation leadership and expenditure for research and development is high, further that participation in OIS led to a shift in the perception of the objectives, needs and conditions of the business and finally the major barriers to the innovation process are a lack of highly motivated people with the necessary technical and business experience.
Keywords: O31; 330; strategic management for Industry 4.0; Open Innovation Session; regional innovation strategy; South Moravian region; innovation barriers; innovation strategy